A graphene-based copper current collector and a method for manufacturing the same
Patent Information
- Application Number
- CN202611364332.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-04
- Publication Date
- 2026-10-30
AI Technical Summary
石墨烯层虽能改善铜集流体的界面均匀性,但其对锂离子的成核诱导能力有限,且结构较为平整;在长期循环中,依然会存在锂枝晶的现象,影响电化学性能
首先,本申请铜掺杂石墨烯分散液涂覆在铜箔表面,热处理,冷却,酸洗活化,形成铜掺杂石墨烯过渡层;其目的在于:可以初步在铜箔表面形成铜掺杂石墨烯过渡层,一方面,经过热处理后,氧化石墨烯被还原成石墨烯,铜金属元素被掺杂到石墨烯中,有利于提高导电性;另一方面,经过铜掺杂后,可以提高与铜箔间的界面结合力,以防止石墨烯剥落,确保界面稳定。在此基础上,经酸洗活化,可在过渡层表面形成微观粗糙结构,提供更多成核活性位点,有利于后续电沉积、热氧化形成花状Cu2O结构;但是,在此过程中,需要控制酸洗活化工艺参数,避免其强氧化性过度氧化铜基体,损害界面稳定性;
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of current collector technology, specifically a graphene-based copper current collector and its preparation method. Background Technology
[0002] Electrodeless lithium batteries have high energy density and are widely used in fields such as electronic energy storage.
[0003] In negative electrodeless lithium batteries, lithium ions are directly deposited and stripped onto the surface of the copper current collector. However, due to the lithium-repellent properties of copper, in practical applications, lithium ions tend to form uneven lithium dendrites when deposited on the copper current collector, which can significantly affect the battery's coulombic efficiency, cycle life, and other electrochemical performance, and may even pose safety hazards.
[0004] To improve the uniform deposition of lithium ions on the surface of copper current collectors, existing technologies typically construct a graphene layer on the copper foil surface. While the graphene layer can improve the interface uniformity of the copper current collector, its ability to induce lithium ion nucleation is limited, and its structure is relatively flat; during long-term cycling, lithium dendrite formation can still occur, affecting electrochemical performance.
[0005] In summary, the preparation of a graphene-based copper current collector and its preparation method are of great significance in order to solve the above problems. Summary of the Invention
[0006] The purpose of this invention is to provide a graphene-based copper current collector and its preparation method to solve the problems mentioned in the background art.
[0007] To solve the above-mentioned technical problems, the present invention provides the following technical solution: A method for preparing a graphene-based copper current collector includes the following steps: Step 1: Add copper-doped graphene to deionized water and disperse to obtain a copper-doped graphene dispersion; Step 2: Coating the copper-doped graphene dispersion onto the surface of a copper foil, heat-treating, cooling, and acid-washing activation to form a copper-doped graphene transition layer, thus obtaining copper current collector A; Step 3: Use a strongly acidic copper sulfate aqueous solution as the electrodeposition solution; electrodeposit copper on the surface of copper current collector A; after electrodeposition, remove the current collector, coat it with a nickel catalyst, and thermally oxidize it to form Cu2O; thus obtaining the copper current collector.
[0008] In a more optimized manner, the Cu2O has a flower-like structure, and the preparation process is as follows: Step 1: Add dilute sulfuric acid to the copper sulfate aqueous solution and adjust the pH to 1.9~2.1 to obtain the electrodeposition solution; Step 2: Set the current density to 12~18 mA / cm² 2Using an electrodeposition solution as the reaction system, electrodeposition was performed on the surface of copper current collector A at room temperature for 50-70 minutes to form a copper layer. Step 3: After electrodeposition is complete, remove the product and apply nickel catalyst to the surface to form an island-like structure; Step 4: In an air atmosphere, set the temperature to 110~130℃ and perform thermal oxidation for 1.5~2.5 hours to form a Cu2O flower-like structure.
[0009] Ideally, the island structure has a diameter of 2-3 mm and a thickness of 0.8-1.2 mm.
[0010] In a more optimized manner, the nickel catalyst is an aqueous slurry comprising flake nickel powder and silicate binder; the viscosity of the aqueous slurry is 400~600 cp.
[0011] Ideally, the solid content of the copper-doped graphene dispersion is 0.1~0.2wt%; and the coating amount of the copper-doped graphene dispersion is 0.02~0.03g / m³. 2 .
[0012] In a more optimized manner, the process parameters for acid washing and activation are: using a 0.4~0.5M perchloric acid aqueous solution, a temperature of 40~60℃, and a time of 1~2h.
[0013] Ideally, the heat treatment temperature is 750~850℃.
[0014] In a more optimized manner, the preparation process of the copper-doped graphene is as follows: add an aqueous solution of graphene oxide and an aqueous solution of copper sulfate to ethanol, disperse, let stand, take the supernatant, separate, purify, and dry to obtain copper-doped graphene.
[0015] In a more optimized manner, the volume ratio of deionized water to ethanol in the raw materials for copper-doped graphene is 1:(6~8), and the mass ratio of graphene oxide to copper sulfate is (0.9~1.2):5.
[0016] Compared with the prior art, the beneficial effects achieved by the present invention are: First, the copper-doped graphene dispersion of this application is coated onto the surface of a copper foil, followed by heat treatment, cooling, and acid pickling activation to form a copper-doped graphene transition layer. The purpose is twofold: firstly, to initially form a copper-doped graphene transition layer on the copper foil surface. On one hand, after heat treatment, graphene oxide is reduced to graphene, and copper metal is incorporated into the graphene, which improves conductivity; secondly, copper doping enhances the interfacial bonding force with the copper foil, preventing graphene peeling and ensuring interfacial stability. Based on this, acid pickling activation forms a micro-rough structure on the transition layer surface, providing more nucleation sites, which is beneficial for subsequent electrodeposition and thermal oxidation to form a flower-like Cu2O structure. However, during this process, it is necessary to control the acid pickling activation process parameters to avoid excessive oxidation of the copper substrate due to its strong oxidizing properties, which could damage interfacial stability. In addition, it is necessary to control the solid content of the copper-doped graphene dispersion because: the specific solid content of this application is beneficial to improving the dispersibility of graphene and inhibiting agglomeration, thereby obtaining a copper-doped graphene transition layer with a relatively uniform thickness after coating; on the other hand, the coating can inhibit the coating cracking during subsequent heat treatment; if the solid content is too high, it will lead to uneven dispersion of graphene in the early stage, which is prone to cracking and affects performance.
[0017] Secondly, since copper-doped graphene itself has a certain degree of lithium-phobicity, which is not conducive to the uniform transport of lithium ions, this application further proposes to electrodeposit copper on the surface of copper-doped graphene, form a specific island structure using a dotted nickel catalyst, and then thermally oxidize it to form a flower-like Cu2O structure. This has the following advantages: On the one hand, Cu2O itself has a certain degree of lithium affinity, which can reduce the lithium nucleation overpotential and guide the uniform deposition of lithium ions, thereby inhibiting the growth of lithium dendrites; on the other hand, Cu2O with a flower-like structure has a higher specific surface area and more active sites than traditional Cu2O layers, which is not only conducive to the full wetting of the electrolyte and the rapid transport of lithium ions, but also can further inhibit dendrites; in addition, it can also buffer the repeated expansion and contraction of the electrode volume during charge and discharge cycles, alleviate the accumulation of internal stress, and thus improve long-term cycle stability.
[0018] Finally, the nickel catalyst can be distributed at the edge of the flower-shaped Cu2O; nickel has certain chemical inertness and conductivity, which is beneficial to improving mechanical strength and conductivity. Mechanical strength is beneficial to maintaining the flower-shaped structure, thereby improving the cycle life of the battery. Detailed Implementation
[0019] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0020] Example 1: A method for preparing a graphene-based copper current collector, comprising the following steps: Step 1: (1) Add 1wt% graphene oxide aqueous solution and 0.02M copper sulfate aqueous solution to ethanol, disperse, let stand, take the supernatant, separate, purify and dry to obtain copper-doped graphene; (2) Disperse copper-doped graphene in deionized water to obtain a copper-doped graphene dispersion with a solid content of 0.1wt%. Step 2: Coating a 0.1 wt% copper-doped graphene dispersion onto the surface of a copper foil at a coating amount of 0.02 g / m², heat-treating at 800 °C, cooling to room temperature, and then washing with a 0.4 M perchloric acid aqueous solution at 40 °C for 1 hour; washing with water and drying to form a copper-doped graphene transition layer, thus obtaining copper current collector A; Step 3: Dissolve 0.4 mol of copper sulfate pentahydrate in deionized water to prepare a 1 L aqueous solution, and adjust the pH to 2.0 with 0.05 M dilute sulfuric acid. Use this solution as the electrodeposition solution, and set the current density to 15 mA / cm². 2 A copper layer was formed by electrodeposition on the surface of copper current collector A at room temperature for 60 min. After electrodeposition, the current collector was removed and a nickel catalyst was dotted on the surface to form an island-like structure with a diameter of 2 mm and a thickness of 0.8 mm. The current collector was then placed in an air atmosphere at a relative humidity of 65% and a temperature of 120 °C for 2 hours to form a Cu2O flower-like structure. The copper current collector was thus obtained. In the above embodiments, the nickel catalyst is an aqueous slurry containing flake nickel powder and silicate binder; its viscosity at room temperature is 500 cp, and its model is Pyro-DuctTM598-C; in the raw material of copper-doped graphene, the volume ratio of deionized water to ethanol is 1:7; and the mass ratio of graphene oxide to copper sulfate is 1:5.
[0021] Example 2: A method for preparing a graphene-based copper current collector, comprising the following steps: Step 1: (1) Add 1wt% graphene oxide aqueous solution and 0.02M copper sulfate aqueous solution to ethanol, disperse, let stand, take the supernatant, separate, purify and dry to obtain copper-doped graphene; (2) Disperse copper-doped graphene in deionized water to obtain a copper-doped graphene dispersion with a solid content of 0.12wt%. Step 2: Coating a 0.12 wt% copper-doped graphene dispersion onto the surface of a copper foil at a coating amount of 0.022 g / m², heat-treating at 800 °C, cooling to room temperature, and then washing with a 0.42 M perchloric acid aqueous solution at 50 °C for 1.2 hours; washing with water and drying to form a copper-doped graphene transition layer, thus obtaining copper current collector A; Step 3: Dissolve 0.4 mol of copper sulfate pentahydrate in deionized water to prepare a 1 L aqueous solution, and adjust the pH to 2.0 with 0.05 M dilute sulfuric acid. Use this solution as the electrodeposition solution, and set the current density to 15 mA / cm². 2 Electrodeposition was performed on the surface of copper current collector A at room temperature for 60 minutes to form a copper layer. After electrodeposition, the surface was removed and coated with nickel catalyst to form an island-like structure with a diameter of 2.2 mm and a thickness of 0.9 mm. The surface was then placed in an air atmosphere at a relative humidity of 65% and a temperature of 120 °C for 2 hours to form a Cu2O flower-like structure, which is the copper current collector. In the above embodiments, the nickel catalyst is an aqueous slurry containing flake nickel powder and silicate binder; its viscosity at room temperature is 500 cp, and its model is Pyro-DuctTM598-C; in the raw material of copper-doped graphene, the volume ratio of deionized water to ethanol is 1:7; and the mass ratio of graphene oxide to copper sulfate is 1:5.
[0022] Example 3: A method for preparing a graphene-based copper current collector, comprising the following steps: Step 1: (1) Add 1wt% graphene oxide aqueous solution and 0.02M copper sulfate aqueous solution to ethanol, disperse, let stand, take the supernatant, separate, purify and dry to obtain copper-doped graphene; (2) Disperse copper-doped graphene in deionized water to obtain a copper-doped graphene dispersion with a solid content of 0.15wt%. Step 2: Coating a 0.15wt% copper-doped graphene dispersion onto the surface of a copper foil at a coating amount of 0.025g / m², heat-treating at 800℃, cooling to room temperature, and then washing with a 0.45M perchloric acid aqueous solution at 50℃ for 1.4 hours; washing with water and drying to form a copper-doped graphene transition layer, thus obtaining copper current collector A; Step 3: Dissolve 0.4 mol of copper sulfate pentahydrate in deionized water to prepare a 1 L aqueous solution, and adjust the pH to 2.0 with 0.05 M dilute sulfuric acid. Use this solution as the electrodeposition solution, and set the current density to 15 mA / cm². 2 Electrodeposition was performed on the surface of copper current collector A at room temperature for 60 minutes to form a copper layer. After electrodeposition, the surface was removed and coated with nickel catalyst to form an island-like structure with a diameter of 2.5 mm and a thickness of 1 mm. The surface was then placed in an air atmosphere at a relative humidity of 65% and a temperature of 120 °C for 2 hours to form a Cu2O flower-like structure, which is the copper current collector. In the above embodiments, the nickel catalyst is an aqueous slurry containing flake nickel powder and silicate binder; its viscosity at room temperature is 500 cp, and its model is Pyro-DuctTM598-C; in the raw material of copper-doped graphene, the volume ratio of deionized water to ethanol is 1:7; and the mass ratio of graphene oxide to copper sulfate is 1:5.
[0023] Example 4: A method for preparing a graphene-based copper current collector, comprising the following steps: Step 1: (1) Add 1wt% graphene oxide aqueous solution and 0.02M copper sulfate aqueous solution to ethanol, disperse, let stand, take the supernatant, separate, purify and dry to obtain copper-doped graphene; (2) Disperse copper-doped graphene in deionized water to obtain a copper-doped graphene dispersion with a solid content of 0.18wt%. Step 2: Coating a 0.18 wt% copper-doped graphene dispersion onto the surface of a copper foil at a coating amount of 0.028 g / m², heat-treating at 800 °C, cooling to room temperature, and then washing with a 0.48 M perchloric acid aqueous solution at 55 °C for 1.8 hours; washing with water and drying to form a copper-doped graphene transition layer, thus obtaining copper current collector A; Step 3: Dissolve 0.4 mol of copper sulfate pentahydrate in deionized water to prepare a 1 L aqueous solution, and adjust the pH to 2.0 with 0.05 M dilute sulfuric acid. Use this solution as the electrodeposition solution, and set the current density to 15 mA / cm². 2 Electrodeposition was performed on the surface of copper current collector A at room temperature for 60 minutes to form a copper layer. After electrodeposition, the surface was removed and coated with nickel catalyst to form an island-like structure with a diameter of 2.8 mm and a thickness of 1.2 mm. The surface was then placed in an air atmosphere at a relative humidity of 65% and a temperature of 120 °C for 2 hours to form a Cu2O flower-like structure, which is the copper current collector. In the above embodiments, the nickel catalyst is an aqueous slurry containing flake nickel powder and silicate binder; its viscosity at room temperature is 500 cp, and its model is Pyro-DuctTM598-C; in the raw material of copper-doped graphene, the volume ratio of deionized water to ethanol is 1:7; and the mass ratio of graphene oxide to copper sulfate is 1:5.
[0024] Example 5: A method for preparing a graphene-based copper current collector, comprising the following steps: Step 1: (1) Add 1wt% graphene oxide aqueous solution and 0.02M copper sulfate aqueous solution to ethanol, disperse, let stand, take the supernatant, separate, purify and dry to obtain copper-doped graphene; (2) Disperse copper-doped graphene in deionized water to obtain a copper-doped graphene dispersion with a solid content of 0.2wt%. Step 2: Coating a 0.2 wt% copper-doped graphene dispersion onto the surface of a copper foil at a coating amount of 0.03 g / m², heat-treating at 800 °C, cooling to room temperature, and then washing with a 0.5 M perchloric acid aqueous solution at 60 °C for 2 hours; washing with water and drying to form a copper-doped graphene transition layer, thus obtaining copper current collector A; Step 3: Dissolve 0.4 mol of copper sulfate pentahydrate in deionized water to prepare a 1 L aqueous solution, and adjust the pH to 2.0 with 0.05 M dilute sulfuric acid. Use this solution as the electrodeposition solution, and set the current density to 15 mA / cm². 2 Electrodeposition was performed on the surface of copper current collector A at room temperature for 60 minutes to form a copper layer. After electrodeposition, the surface was removed and coated with nickel catalyst to form an island-like structure with a diameter of 3 mm and a thickness of 1.2 mm. The surface was then heated at 120 °C with a relative humidity of 65% for 2 hours in an air atmosphere to form a Cu2O flower-like structure, which is the copper current collector. In the above embodiments, the nickel catalyst is an aqueous slurry containing flake nickel powder and silicate binder; its viscosity at room temperature is 500 cp, and its model is Pyro-DuctTM598-C; in the raw material of copper-doped graphene, the volume ratio of deionized water to ethanol is 1:7; and the mass ratio of graphene oxide to copper sulfate is 1:5.
[0025] Comparative Example 1: Copper foil was used as the copper current collector.
[0026] Comparative Example 2: Graphene layer only; the rest is the same as in Example 3; the specific differences are as follows: Graphene oxide was added to deionized water to obtain a graphene oxide dispersion with a solid content of 0.15wt%; it was coated on the surface of copper foil with a coating amount of 0.025g / m², heat-treated at 800°C, cooled to room temperature, and then washed at 50°C for 1 hour with a 0.45M perchloric acid aqueous solution; washed with water and dried to form a graphene layer, thus obtaining a copper current collector.
[0027] Comparative Example 3: Graphene transition layer without copper doping; otherwise the same as Example 3; specific differences are as follows: Step 1: Wash the copper foil with a 0.45M perchloric acid aqueous solution at 50°C for 1.4 hours; wash with water and dry; to obtain pretreated copper foil; Step 2: Dissolve 0.4 mol of copper sulfate pentahydrate in deionized water to prepare a 1 L aqueous solution, and adjust the pH to 2.0 with 0.05 M dilute sulfuric acid. Use this solution as the electrodeposition solution, and set the current density to 15 mA / cm². 2 Electrodeposition was performed on the pretreated copper foil surface at room temperature for 60 minutes to form a copper layer. After electrodeposition, the foil was removed and a nickel catalyst was dotted on the surface to form an island-like structure with a diameter of 2.5 mm and a thickness of 1 mm. The foil was then placed in an air atmosphere at a relative humidity of 65% and a temperature of 120 °C for 2 hours to form a Cu2O flower-like structure, which is the copper current collector.
[0028] Comparative Example 4: No acid washing or activation was performed; otherwise, it was the same as Example 3; the specific differences are as follows: Step 1: (1) Add 1wt% graphene oxide aqueous solution and 0.02M copper sulfate aqueous solution to ethanol, disperse, let stand, take the supernatant, separate, purify and dry to obtain copper-doped graphene; (2) Disperse copper-doped graphene in deionized water to obtain a copper-doped graphene dispersion with a solid content of 0.15wt%. Step 2: Coating a 0.15wt% copper-doped graphene dispersion onto the surface of a copper foil with a coating amount of 0.025g / m², heat-treating at 800℃, and cooling to room temperature to form a copper-doped graphene transition layer, thus obtaining copper current collector A. Step 3: Dissolve 0.4 mol of copper sulfate pentahydrate in deionized water to prepare a 1 L aqueous solution, and adjust the pH to 2.0 with 0.05 M dilute sulfuric acid. Use this solution as the electrodeposition solution, and set the current density to 15 mA / cm². 2 Electrodeposition was performed on the surface of copper current collector A at room temperature for 60 minutes to form a copper layer. After the electrodeposition was completed, the copper current collector was removed and a nickel catalyst was dotted on the surface to form an island-like structure with a diameter of 2.5 mm and a thickness of 1 mm. The current collector was then placed in an air atmosphere at a relative humidity of 65% and a temperature of 120 °C for 2 hours to form a Cu2O flower-like structure, which is the copper current collector.
[0029] Comparative Example 5: The solid content of the copper-doped graphene dispersion was too high; otherwise, it was the same as in Example 3; the specific differences are as follows: Step 1: (1) Add 1wt% graphene oxide aqueous solution and 0.02M copper sulfate aqueous solution to ethanol, disperse, let stand, take the supernatant, separate, purify and dry to obtain copper-doped graphene; (2) Disperse copper-doped graphene in deionized water to obtain a copper-doped graphene dispersion with a solid content of 0.8wt%. Step 2: Coating a copper-doped graphene dispersion of 0.8 wt% onto the surface of a copper foil at a coating amount of 0.025 g / m², heat-treating at 800 °C, cooling to room temperature, and then washing with a 0.45 M perchloric acid aqueous solution at 50 °C for 1.4 hours; washing with water and drying to form a copper-doped graphene transition layer, thus obtaining copper current collector A; Step 3: Dissolve 0.4 mol of copper sulfate pentahydrate in deionized water to prepare a 1 L aqueous solution, and adjust the pH to 2.0 with 0.05 M dilute sulfuric acid. Use this solution as the electrodeposition solution, and set the current density to 15 mA / cm². 2 Electrodeposition was performed on the surface of copper current collector A at room temperature for 60 minutes to form a copper layer. After the electrodeposition was completed, the copper current collector was removed and a nickel catalyst was dotted on the surface to form an island-like structure with a diameter of 2.5 mm and a thickness of 1 mm. The current collector was then placed in an air atmosphere at a relative humidity of 65% and a temperature of 120 °C for 2 hours to form a Cu2O flower-like structure, which is the copper current collector.
[0030] Comparative Example 6: No flower-like Cu2O structure, only a conventional Cu2O layer; otherwise the same as Example 3; specific differences are as follows: Step 1: (1) Add 1wt% graphene oxide aqueous solution and 0.02M copper sulfate aqueous solution to ethanol, disperse, let stand, take the supernatant, separate, purify and dry to obtain copper-doped graphene; (2) Disperse copper-doped graphene in deionized water to obtain a copper-doped graphene dispersion with a solid content of 0.15wt%. Step 2: Coating a 0.15wt% copper-doped graphene dispersion onto the surface of a copper foil at a coating amount of 0.025g / m², heat-treating at 800℃, cooling to room temperature, and then washing with a 0.45M perchloric acid aqueous solution at 50℃ for 1.4 hours; washing with water and drying to form a copper-doped graphene transition layer, thus obtaining copper current collector A; Step 3: Dissolve 0.4 mol of copper sulfate pentahydrate in deionized water to prepare a 1 L aqueous solution, and adjust the pH to 2.0 with 0.05 M dilute sulfuric acid. Use this solution as the electrodeposition solution, and set the current density to 15 mA / cm². 2 A copper layer was formed by electrodeposition on the surface of copper current collector A at room temperature for 60 minutes; then, it was thermally oxidized at 220°C for 2 hours in air atmosphere and cooled to form a Cu2O layer, thus obtaining the copper current collector.
[0031] Performance Test 1: The copper current collectors prepared in Examples 1-5 and Comparative Examples 1-6 were assembled into a 2032 type full cell. The assembly process was as follows: LFP, SP, PVDF, and VGCF were added to NMP in a mass ratio of 85:7:7:1 and stirred to obtain a positive electrode slurry; the positive electrode slurry was coated on the surface of aluminum foil and dried at 60°C for 12 hours, followed by drying at 120°C for 1 hour to obtain a positive electrode sheet; and the negative electrode shell, copper current collector, PE separator, positive electrode sheet, and positive electrode shell were assembled in that order to obtain a 2032 type full cell. In the above assembly, the electrolyte is 3M lithium bis(fluorosulfonyl)imide / 1,2-dimethoxyethane-tetrafluoroethyltetrafluoropropyl ether (volume ratio 8:2) and 1% fluoroethylene carbonate; wherein, LFP is lithium iron phosphate, the active material; SP is conductive carbon black, the conductive agent; PVDF is polyvinylidene fluoride, the binder; and VGCF is conductive fiber, the conductive agent.
[0032] The above-obtained electrodeless lithium battery was tested at a rate of 0.5C / 0.5C for 300 cycles, and the capacity retention and average coulombic efficiency were tested; the test results are shown in Table 1. Table 1
[0033] Conclusions: The data in Table 1 show that the copper current collector prepared in this application can suppress lithium dendrites and improve the electrochemical performance of the battery. According to Comparative Example 1, using copper foil as the current collector results in lithium dendrite formation and very poor overall performance. According to Comparative Example 2, only a graphene layer is used, without copper doping or flower-like Cu2O, leading to a decrease in overall performance. According to Comparative Example 3, the absence of a copper-doped graphene transition layer, coupled with poor adhesion and easy peeling of the subsequent Cu2O flower-like structure, results in a decrease in overall performance. According to Comparative Example 4, without acid washing and activation, the overall performance decreases. According to Comparative Example 5, the excessive solid content in the copper-doped graphene dispersion leads to uneven dispersion and cracking, resulting in a decrease in overall performance. According to Comparative Example 6, the absence of a flower-like Cu2O structure, with only a traditional Cu2O layer, results in a small specific surface area, poor lithiophilicity, and poor buffering capacity for volume expansion, leading to a decrease in overall performance.
[0034] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a graphene-based copper current collector, characterized in that: Includes the following steps: Step 1: Add copper-doped graphene to deionized water and disperse to obtain a copper-doped graphene dispersion; Step 2: Coating the copper-doped graphene dispersion onto the surface of a copper foil, heat-treating, cooling, and acid-washing activation to form a copper-doped graphene transition layer, thus obtaining copper current collector A; Step 3: Use a strongly acidic copper sulfate aqueous solution as the electrodeposition solution; electrodeposit copper on the surface of copper current collector A; after electrodeposition, remove the current collector, coat it with a nickel catalyst, and thermally oxidize it to form Cu2O; thus obtaining the copper current collector.
2. The method for preparing a graphene-based copper current collector according to claim 1, characterized in that: The Cu2O has a flower-like structure, and the preparation process is as follows: Step 1: Add dilute sulfuric acid to the copper sulfate aqueous solution and adjust the pH to 1.9~2.1 to obtain the electrodeposition solution; Step 2: Set the current density to 12~18 mA / cm² 2 Using an electrodeposition solution as the reaction system, electrodeposition was performed on the surface of copper current collector A at room temperature for 50-70 minutes to form a copper layer. Step 3: After electrodeposition is complete, remove the product and apply nickel catalyst to the surface to form an island-like structure; Step 4: In an air atmosphere, set the temperature to 110~130℃ and perform thermal oxidation for 1.5~2.5 hours to form a Cu2O flower-like structure.
3. The method for preparing a graphene-based copper current collector according to claim 2, characterized in that: The island-shaped structure has a diameter of 2-3 mm and a thickness of 0.8-1.2 mm.
4. The method for preparing a graphene-based copper current collector according to claim 2, characterized in that: The nickel catalyst is an aqueous slurry containing flake nickel powder and silicate binder; the viscosity of the aqueous slurry is 400~600cp.
5. The method for preparing a graphene-based copper current collector according to claim 1, characterized in that: The solid content of the copper-doped graphene dispersion is 0.1~0.2wt%; the coating amount of the copper-doped graphene dispersion is 0.02~0.03g / m³. 2 .
6. The method for preparing a graphene-based copper current collector according to claim 1, characterized in that: The process parameters for acid pickling and activation are as follows: using a 0.4~0.5M perchloric acid aqueous solution, at a temperature of 40~60℃, for a time of 1~2h.
7. The method for preparing a graphene-based copper current collector according to claim 1, characterized in that: The heat treatment temperature is 750~850℃.
8. The method for preparing a graphene-based copper current collector according to claim 1, characterized in that: The preparation process of copper-doped graphene is as follows: add aqueous solutions of graphene oxide and copper sulfate to ethanol, disperse, let stand, take the supernatant, separate, purify and dry to obtain copper-doped graphene.
9. The method for preparing a graphene-based copper current collector according to claim 8, characterized in that: In the raw materials for copper-doped graphene, the volume ratio of deionized water to ethanol is 1:(6~8), and the mass ratio of graphene oxide to copper sulfate is (0.9~1.2):
5.
10. A copper current collector prepared by a method for preparing a graphene-based copper current collector according to any one of claims 1 to 9.
